Chapter 3D Visualization: Revealing Imagery Space by Technological Parameter - Sosna, Nina (Proceedings e report, 2018)
The paper examines several examples of visualization common to the contemporary Russian scene, which 1) follow the long tradition of elaborating texts; 2) are developed on the border between the science of geography and visual art; 3) belong to the sphere of amateur production that by trial and error method propose a special 3D filming as a proper way to present an archive. Among other projects concerned with questions of memory work and its visual presentation, it is the latter one that orients itself towards the possibilities of the future.